Chromate removal from aqueous solution using layered double hydroxides beads. - Nhat Ha, Ho Nguyen; Mai Tho, Nguyen Thi; Thang, Tran Ngoc; An, Tran Boi; Viet, Van; Kha, Nguyen Binh; Du, Cao Van; Minh, Bui Quang; Phuong Dieu, Nguyen Thi; Kim Phuong, Nguyen Thi (Vietnam Journal of Chemistry, 2016)
In this study, a novel layered double hydroxides beads (LDHs beads) were developed for removal of chromium. The LDHs beads (MgAl beads and MgFe beads) were generated by impregnating synthetic MgFe-Cl (2:1) and MgAl-Cl (2:1) into alginate/poly(vinyl alcohol)-glutaraldehyde gel bead. The adsorption of chromate (Cr(VI)) onto the 8 % LDHs beads was investigated by performing both equilibrium and kinetic batch tests. Equilibrium tests showed that adsorption of chromate followed Langmuir isotherm and that the 8 % LDHs beads were capable of removing chromate (qm = 1.3912-1.4380 mg Cr.g-1). It was further revealed from kinetic tests that removal efficiency of chromate was 92.50 % for 8 % MgAl beads and 90.01 % for 8 % MgFe beads at the initial chromate concentrations of 45 mg Cr.L-1. This indicates that the 8 % LDHs beads developed in this study can be used as promising adsorbents for simultaneous removal of chromate from industrial wastewater or groundwater containing these contaminants. Keywords. Layered double hydroxides beads, chromate removal, adsorption, kinetics, isotherm.